(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This article examines the challenges of organizing extracurricular learning activities for general secondary school students and explores the potential of adopting an activity-based approach in this context. It highlights how this pedagogical method can enhance independent learning, support cognitive development, and integrate modern educational technologies into extracurricular programs.